Digital healthcare industry and technology trends - Han, Jeong Hyeon; Lee, Joo Yeoun (Proceedings - 2021 IEEE International Conference on Big Data and Smart Computing, BigComp 2021, 2021)
Healthcare is an enormous industry based on legacy systems, which can lead to inefficiencies. While governments and medical companies have long been the main investors, major tech companies including Google, Microsoft have started investing more into digital health. Moreover, with the global pandemic of COVID-19 around the world, discussions about digital healthcare are once again emerging. This has caused a major shift in areas of focus within digital health as new technologies emerge and regulations evolve due to combined expertise. In this paper, we will look at the digital healthcare industry, policies, and technologies.
Keywords: Healthcare industry; Industry based; Medical companies; MicroSoft; Technology trends; AI; Big Data; Digital healthcare; Healthcare